Study on tissue culture conditions of Maesa balansae Mez. for mass production - Lien, Quach Thi; Thanh, Nguyen Duc (Academia Journal of Biology, 2015)
Maesa balansae Mez. is a valuable herb, which has been used in traditional vietnamese medicine. A mixture of antiprotozoal saponins was isolated from the leaves of Maesa balansae Mez. In this paper, we report the results of the study on tissue culture conditions for this plant. The Maesa tissue culture was carried out in MS medium, supplemented with auxin and cytokinine in different concentrations and combinations. All of the 8 investigated culture media were suitable for mass production of Maesa and its bioactive components. However, the SK7 medium (MS + 1 mg/l NAA + 2 mg/l BAP) and the SK8 medium (MS + 1 mg/l NAA + 4 mg/l BAP) were the most efficient.